Persatuan Teknologi Komputer (Petakom) Portal Management System (Ppms) - Narresh Naidu, Subramaniam (2022)
Persatuan Teknologi Komputer (PETAKOM) Portal Management System (PPMS) has been developed to provide a web-based portal administration system for PETAKOM. PPMS enables PETAKOM to administer the club's activities in an organized manner via the portal, as well as to deliver information that may be presented depending on the preferences of the Faculty of Computing (FK) students. The rapid application development technique was selected as the development methodology for this system. This technique was selected because iterations allow for easy improvement. The system's design will be based on existing information providing portals from other current real-life systems. Since this system is user-friendly, the user will be able to rapidly comprehend the system and do the required activity rather than wasting time learning on how to use the system. The system's user interface would be simple and responsive. The implemented system can perform a wide range of functions. The system also allows FK student to book PETAKOM room for any occasions. Aside from that, another module enables FK Students to lodge complaints regarding the organization or Faculty via the portal. Following that, PETAKOM can disseminate information about programs and events via the site, ensuring that FK students do not miss out on any information. Finally, PETAKOM can manage merchandise through the portal as well enabling FK students to purchase the merchants.